Wartime Vascular Injury. (5th September 2018) - Rasmussen, Todd; Stockinger, Zsolt; Antevil, Jared; White, Christopher; Fernandez, Nathaniel; White, Joseph; White, Paul
Abstract: Wartime vascular injury can be particularly challenging due to the complexity of the case, concomitant injuries, resource limitations, and often lack of expertise of the operating surgeon. The proliferation of vascular shunting has been of particular importance as a damage control surgery technique to restore perfusion and temporize the immediate need for definitive repair necessary for limb salvage, particularly in austere locations. Diagnosis of vascular injury can be made using a variety of techniques, from physical examination to ankle–brachial indices to the use of CT angiography or invasive angiographic techniques. Operative planning and judgment are therefore critical in deciding both how and whether to operate. Surgeons likely to deploy should take every opportunity to practice vascular exposures and techniques through clinical practice and laboratory courses.